Reform of State Administrative Law from the Perspective of Fiqh Siyasah on Public Services to Achieve Good Governance in Indonesia - Adzanah Mariska Salsabila (Siyasah Wa Qanuniyah, 2025)
Quality public services are a key pillar in realizing good governance. However, government administration practices in Indonesia still face various obstacles in implementing this principle. This study aims to analyze the urgency of reforming state administrative law from the perspective of fiqh siyasah (Islamic political jurisprudence) on public services in Indonesia. The method used is normative juridical research with a legislative, conceptual, and theological-normative approach, through a literature review of legal and fiqh siyasah literature. The results of the study indicate the need to integrate Islamic values such as justice (al-'adl), benefit (al-maslahah), and trustworthiness (amanah) in the delivery of public services in order to strengthen the principle of good governance. The novelty of this study lies in the combination of the modern state administrative law paradigm and fiqh siyasah, which provides a conceptual contribution to the renewal of the administrative law and public service systems in Indonesia.